Does Hepatic Periarteriei Neuorectomy Prevent the A/terations That Occur in Dog Urotheiium at Eariy Follow up Following Portocaval Anastomosis? (Annals of Medical Research, 2021)
None
Keywords: s : Portocaval anastomosis, urothelial carcinogenesis.